Factors of Doctor’s Emphaty in the Successful Treatment of Patients - Irma Binarti; Pindobilowo; Vicka Dwi Reformatika (Formosa Journal of Applied Sciences, 2023)
Empathy is closely related to the field of Health and plays an important role in patient health relationships. Empathy is the standard of the therapeutic relationship between doctors and patients, according to research it has been proven that empathy affects patient care outcomes. By using a literature study approach to various research results and other literature, this journal aims to provide an overview of doctors' empathy factors in treating patients based on various scientific literature related to research results that have been carried out. Based on the results of the study, it can be seen that the attitude of doctors towards patients when performing treatment is one of the keys to the success of patient care. If doctors experience obstacles in showing empathy, the success of patient care will decrease, and vice versa